APLIKASI SISTEM INFORMASI PERSEDIAN BARANG DAN PIUTANG DAGANG ONLINE BERBASIS CLOUD PADA PD KURNIA - Sabarudin Hidayah, Elis Sondang Dasawaty (Institut Bisnis dan Informatika Kwik Kian Gie, 2018)
Information technology business needs will continue to increase, especially in companies with high levels of routine and have a lot of data that must be processed as a trading company. The information system is used today by many trading companies have not had a significant impact on the relationship with the customer. Inventory management is not maximized and the lack of control of the customer's accounts receivable.Cloud is a computing model in which software and in some cases the virtual hardware resources that are provided as a service over the internet. The system was developed using CodeIgniter framework that has an MVC (Model View Controller) architecture with the PHP language. The database used is MySQL.The technique of collecting data for this research were obtained from a non-participant observation, interviews and literature studies. To analyze and design applications, workflow and processes on the system of inventory and accounts receivable information represented by the data flow diagrams, use case diagrams, sequence diagrams, activity diagram and Entity Relationship Diagram.The Results from this research is the information system of inventory and accounts receivable based on cloud where PD Kurnia as Wholesale able to check the inventory of the customer (member) purchased from PD Kurnia well as submit bids, and vice versa customers can view inventory PD Kurnia and book by online. PD Kurnia through this system can perform control of accounts receivable to customers.The information system of inventory and accounts receivable PD Kurnia and also facilitate its customers in managing inventory and accounts receivable. The bidding process for goods and warning of repayment can be done easily by PD Kurnia, and ordering of goods by the customer to PD Kurnia can be done more quickly and reduce the risk of a booking error.Keywords: Systems, Trading Company, Inventory, Accounts Receivable, Cloud